Fat, total solids and solids-not-fat percentage of milk in Vechur cattle - Venkatachalapathi, R Thirupathi; Iype, Sosama (The Indian Journal of Animal Sciences, 2012)
Milk samples from 15 Vechur cows were collected at weekly intervals in the morning and evening for one lactationand analysed for percentage of fat, total solids and solids-not-fat. The average percentage of milk fat, total solids andsolids-non-fat trom 1 to 44 weeks were 5.95± 0.12 and 6.62± 0.13, 14.79± 0.13 and 15.53 ±0.12, 8.84± 0.12.and 8.92± 0.14 for morning and evening respectively. The fat and total solids percentage of the milk showed an increasing trendas the lactation advanced. Solids-not-fat percentage was not having any trend during stage of lactation. Least - squaresanalysis of variance showed highly significant effect of time of milking and stage of lactation on fat, and total solidspercentage and the differences in solids-not-fat percentage was not significant. The least squares mean for 1 to 44 weekswere 6.13 ±90.12, 15.02 ±0.14 and 8.89 ± 0.13 for fat, total solids and solids-not-fat percentage respectively.